2022
DOI: 10.1097/ta.0000000000003807
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism risk after spinal cord injury: A secondary analysis of the CLOTT study

Abstract: Spinal cord injury patients are at high risk of VTE. Early initiation of prophylaxis is associate with lower VTE rates. Delayed initiation of prophylaxis, heparin, and missed doses are associated with increased risk of VTE and represent targets for quality improvement measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
(78 reference statements)
0
13
0
Order By: Relevance
“…Even when best-practice prophylaxis is prescribed to trauma patients, nonadministration of regular pharmacologic prophylaxis may limit their effectiveness. Numerous studies have shown the association of VTE events with missed doses of VTE prophylaxis 7,8,38,39 . We must continuously strive for all steps of defect-free care to include evidence-based risk assessment, prescription of optimal prophylaxis, and administration of all prescribed doses of prophylaxis 31 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even when best-practice prophylaxis is prescribed to trauma patients, nonadministration of regular pharmacologic prophylaxis may limit their effectiveness. Numerous studies have shown the association of VTE events with missed doses of VTE prophylaxis 7,8,38,39 . We must continuously strive for all steps of defect-free care to include evidence-based risk assessment, prescription of optimal prophylaxis, and administration of all prescribed doses of prophylaxis 31 .…”
mentioning
confidence: 99%
“…Numerous studies have shown the association of VTE events with missed doses of VTE prophylaxis. 7,8,38,39 We must continuously strive for all steps of defect-free care to include evidence-based risk assessment, prescription of optimal prophylaxis, and administration of all prescribed doses of prophylaxis. 31 Missed of VTE prophylaxis have been commonly identified at large academic hospitals (including trauma centers), as well as community hospitals.…”
mentioning
confidence: 99%
“…Secondary analysis of the Consortium Leaders in the Study of Traumatic Thromboembolism (CLOTT) trial indicated improved VTE events in spinal cord injuries with early use of LMWH. 13 Applying the results of the CLOTT trial which was primarily comprised of young patients (mean age = 29.0 years) may be challenging at other trauma centers. 14 For example, the traumatic spine surgery practice at MMC with older patient population is oriented toward early UFH use.…”
Section: Discussionmentioning
confidence: 99%
“…Both societies emphasize that thromboprophylaxis should be continuous and without interruption. Missed doses of VTE prophylaxis are significantly associated with increased risk of VTE 59,60 . Furthermore, the practice of holding pharmacologic prophylaxis for surgical procedures out of fear of bleeding complication is not based on evidence.…”
Section: Current Guidelines For Optimal Vte Prophylaxis After Traumamentioning
confidence: 99%
“…Missed doses of VTE prophylaxis are significantly associated with increased risk of VTE. 59,60 Furthermore, the practice of holding pharmacologic prophylaxis for surgical procedures out of fear of bleeding complication is not based on evidence. In Geerts' 1996 landmark trial, prophylaxis was not withheld for surgical procedures except for spinal fixation (for which only one preoperative dose was held).…”
Section: Missed Doses Of Pharmacologic Vte Prophylaxismentioning
confidence: 99%